Mentoring in Academe: A Feminist Poststructural Lens on Stories of Women Engineering Faculty of Color - Buzzanell, Patrice M.; Long, Ziyu; Anderson, Lindsey B.; Kokini, Klod; Batra, Jennifer C. (Management communication quarterly, 2015)
We analyzed the mentoring narratives of women of color in faculty in engineering using feminist poststructural narratological lenses. We found that university mentoring systems were designed to align with master narratives of mentoring but did not coincide with women faculty’s own mentoring stories. Specifically, women engineers regarded their mentee experiences and cultures of mentoring with varying levels of suspicion, ambiguity, vulnerability, and dis/enchantment that became embodied in alternative subject positions, emplotments, and agency. We contribute to greater understandings of mentoring processes as well as difference and inclusion in science, technology, engineering, and math (STEM) academic workplaces.